ANALYSIS OF THE RELATIONSHIP BETWEEN SLAKE DURABILITY AND THE DISPERSIVITY POTENTIAL OF CLAY SHALE BOGOR - Aven Polin Power Manalu; Hendy Wijaya; Ali Iskandar; Bernard Sumarlin (JMTS: Jurnal Mitra Teknik Sipil, 2026)
Clay shale is a material which is highly slaking, and is commonly assumed to be dispersive. Investigations related to the correlation between slake durability and soil dispersivity, are however, rather sparse. The aim of this research is to examine the relationship between slake durability and dispersivity properties of clay shale obtained from Sentul City, Bogor, Indonesia. Laboratory tests were performed using slake durability, pinhole, crumb and double hydrometer test. The results show that the durability of the clay shale is low, with an average second cycle durability index (Id₂) of 45,95%. The pinhole test gave a result of non-dispersive to slightly dispersive (ND3 – ND2), which corresponds to effluent that is clear to slightly turbid with a final hole diameter less than 2,5 mm. However, the double hydrometer analysis gave a dispersion percentage of 84,85%, and the crumb test gave moderate to high dispersivity. The results indicate that, low slake durability does not necessarily mean high soil dispersivity. A pinhole test is still considered the most representative test to identify dispersive soils, and offers valuable information for the development of resilient infrastructure in regions where clay shale deposits are present. Abstrak Clay shale merupakan material yang rentan terhadap pelapukan (slaking) dan sering diasumsikan memiliki perilaku dispersif ketika terkena air. Namun, penelitian mengenai hubungan antara ketahanan pelapukan dan dispersivitas tanah masih terbatas. Penelitian ini bertujuan untuk menganalisis hubungan antara ketahanan pelapukan dan potensi dispersivitas clay shale dari Sentul City, Bogor, Indonesia. Pengujian laboratorium dilakukan melalui uji slake durability, pinhole, crumb, dan hidrometer ganda. Hasil penelitian menunjukkan bahwa clay shale memiliki nilai rata-rata indeks durabilitas siklus kedua (Id₂) sebesar 45,95% yang termasuk kategori durabilitas rendah . Hasil uji pinhole mengklasifikasikan material sebagai non-dispersif hingga sedikit dispersif (ND3–ND2), ditunjukkan oleh aliran keluar yang jernih hingga sedikit keruh dan diameter akhir lubang kurang dari 2,5 mm. Sebaliknya, analisis hidrometer ganda menghasilkan persentase dispersi sebesar 84,85%, sedangkan uji crumb menunjukkan dispersivitas sedang hingga tinggi. Hasil penelitian menunjukkan bahwa ketahanan pelapukan yang rendah tidak selalu menunjukkan tingkat dispersivitas yang tinggi. Uji pinhole tetap menjadi metode yang paling representatif dalam identifikasi tanah dispersif, serta memberikan informasi yang bermanfaat untuk mendukung pengembangan infrastruktur yang tangguh pada wilayah dengan endapan clay shale.